(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this retrospective study was to evaluate the possible complications and the complication management of cervical anterior discectomies and fusions in light of the literature.Materials and Methods: The study population consisted of patients who presented to the clinic with neck pain and/or arm pain, loss of strength, and sensory disturbances who were operated on after a lack of response to conservative/medical treatment. This study included 200 cervical discopathy and/or cervical spondylosis cases. The literature review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta‑analyses guidelines without language or country restrictions.Results: The most common complication was dysphagia. The complications also included dural tears, cerebrospinal fluid leakage, graft extrusions, neurological deterioration, postoperative hematomas, and recurrent laryngeal nerve injuries. These were found to be consistent with the literature.Conclusion: In order to minimize the incidence of complications, the preoperative clinical examinations and radiological imaging of each patient should be examined carefully, and the appropriate surgical planning should be performed. It is also important to comply with the rules of asepsis and antisepsis, make sure the surgical time is as short as possible, and perform a dissection based on the patient’s anatomy with the appropriate surgical equipment. In addition, it is important to wash the surgical area frequently, drain the system at the end of the operation, close the tissues in accordance with anatomical integrity, and perform close clinical follow-ups.Keywords: Anterior cervical discectomy and fusion; cervical degenerative disc disease; complications; management of complications.